Influence of chicken feather on the rheological properties and performance of modified asphalts. (20th December 2020) - Rivera-Armenta, José Luis; Salazar-Cruz, Beatriz Adriana; Chávez-Cinco, María Yolanda; Morales-Cepeda, Ana Beatriz; Zapién-Castillo, Samuel
Graphical abstract: Highlights: Chicken feather copolymer particles were added as asphalt modifier for first time. Rheological behavior of ACFBP is similar to that using SBS, at same concentration. The functional groups of CFBP interact with asphalt fractions to decrease the storage stability. There is a critical concentration of CFBP as modifier in asphalt. Abstract: One of the most significant applications of modified asphalts is the asphalt pavement design industry. Asphalts are mainly modified by using polymeric materials; however, the actual increase in organic waste materials demands that special attention be paid on their management and final disposal. As a consequence, attractive alternatives involving reusing organic wastes, such as in asphalt modification technology, have emerged as efficient ways of handling them. Chicken feathers (CF) are considered as organic waste material from the chicken breeding industry. Incorporating CF into asphalt can reduce problems in pavement design due to its economic, technical, and ecological advantages. This work studies the effect of adding chicken feather bioparticles (CFBP) into asphalt, taking a mixture of asphalt modified with radial-structured styrene–butadienestyrene copolymer (SBS) as a reference. Preliminary tests were carried out in order to establish the experimental limitations due to the unknown properties of the CFBP. The rheological behavior of asphalt-polymer blends (AP) and asphalt-bioparticles mixtures (ACFBP) at 2, 4, and 6 wt%, were evaluated. Modified asphalt blends resulted in improved rheological properties such as complex modulus (G*), elastic modulus (G′), viscous modulus (G″), as well as in the reduction of the phase angle (δ), which has been related to better resistance to permanent deformations. The behavior of the ACFBP blend at 2% was comparable to that of AP blend at the same modifier concentration; however, ACFBP showed better storage stability, which is a relevant result considering that phase separation is one of the main obstacles for using SBS in paving technology. According to the overall results, modifying asphalt with CFBP is not only a more sustainable and cleaner way of producing surface roads, but it also may lead to cost reduction, due to the potential replacement of synthetic polymer with organic waste, without affecting the final properties of the asphalt blend.